2014
DOI: 10.1186/s12939-014-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the turnover intention of Chinese village doctors based on the investigation results of Xiangyang City in Hubei Province

Abstract: IntroductionThis study analyzes the factors that influence the turnover intention of village doctors by investigating village clinic workers in rural areas, particularly in Xiangyang City, Hubei Province.MethodsA total of 1184 village clinics were sampled randomly in Xiangyang City. The research assistants distributed 1930 questionnaires to village doctors. This study had a response rate of 97.88%. A total of 1889 village doctors completed the questionnaires.ResultsThe results of the investigation conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 25 publications
9
55
0
1
Order By: Relevance
“…Since the training of doctors requires a long-term education and practice [13], high turnover tendency may lead to huge transition costs and serious loss of patients' confidence, which is a serious problem for the stability of hospitals and the medical system [14,15]. Numerous studies have analysed the influencing factors of doctors' turnover intention, including a country's medical system, occupational environment, doctor-patient relationship, level of employment and alternative job opportunities, and other external environmental factors [3,[16][17][18]. Internal individual factors include gender, age, marital status and work ability [4,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the training of doctors requires a long-term education and practice [13], high turnover tendency may lead to huge transition costs and serious loss of patients' confidence, which is a serious problem for the stability of hospitals and the medical system [14,15]. Numerous studies have analysed the influencing factors of doctors' turnover intention, including a country's medical system, occupational environment, doctor-patient relationship, level of employment and alternative job opportunities, and other external environmental factors [3,[16][17][18]. Internal individual factors include gender, age, marital status and work ability [4,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, these researches have not involve the impact of resilience. At the same time, the existing studies have mostly used the ttest, Analysis of Variance (ANOVA) and chi-square test, as well as multivariate statistical analysis to analyse the influencing factors of turnover intention [3,4,[16][17][18][19][20][21][22]. Structural Equation Modelling (SEM) can not only accurately and quantitatively measure the correlation between observed variables, but also track and deeply dig the correlation between latent variables, and even the causal relationship between measured variables.…”
Section: Introductionmentioning
confidence: 99%
“…The only research on this topic was carried out in one province and suggested that the job satisfaction of village doctors was low [18]. However, it did not discuss the relevant policy factors and how they affect job satisfaction and using data from only one province ignores the varied economic status and health reform processes among different areas of China [1921]. The purpose of this mixed-method study is to describe village doctors’ job satisfaction under the context of health sector reform and investigate the associated factors, using a survey data from three provinces.…”
Section: Introductionmentioning
confidence: 99%
“…With the current level of rapid economic growth and social development, China's health system faces new challenges, such as the increased demands and expenditures for health care, inefficient use of health care resources, and an imbalanced distribution of the medical workforce. The central government of China passed a landmark program related to the health system in 2009, which was aimed at improving both health care for all citizens by strengthening disease control and the primary care system [1, 2]. The new medical reform program calls for building “a strong rural health service network while improving the wages of rural doctors.”…”
Section: Introductionmentioning
confidence: 99%